PENGARUH RASIO CAMEL TERHADAP RETURN SAHAM - ALIT SUARDANA, KETUT (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 4 No 2 (2009))
Financial performance is one of fundamental aspects in evaluating a company condition. This research aims to evaluate bank performance based on current regulation and to examine the effect of financial ratios CAMEL on stock return. Data are analyzed using multiple regressions, and the result shows that CAMEL ratios have positive effect on stock return. However, partially only CAR ratio affect the stock return.
Keywords: ROA, CAR, LDR, BOPO, stock return